Sensible social support and its relation to the psychological security of divorcees in Kafr Kassem - Al Rowad, Thiab Mohamed; Bedair, Tahani Rizk Ali (Journal of Educational and Psychological Sciences, 2017)
The aim of this study was to identify the perceived social support and its relation to the psychological security of divorced women in the light of age variables and scientific qualification. The study sample consisted of (170) divorced women in Kafr Kassem area in Palestine during the second half of the year (2016). To achieve the objectives of the study, the perceived social support scale and psychological security measure were used. The results showed an average level of perceived social support and psychological security for divorcees in Kafr Qasim. The results showed statistically significant differences in the level of perceived social support due to the variable of scientific qualification and for those with university qualification, and there were no statistically significant differences in the level of perceived social support due to the variable age. The results showed that there is no statistically significant difference in the level of psychological security attributed to the age variables and the scientific qualification. The results also showed a positive correlation between the social support and psychological security of divorcees in Kafr Kassem. The study recommends more social support and psychological security for divorcees.
Keywords: perceived social; support; psychological security; divorced women; Kafr Qasem